ANALYSIS OF PROMOTIONAL MEDIA ON TIKTOK ACCOUNT @ SURABAYA ZOO (KBS) IN INCREASING VISITOR INTEREST - Arya Nugaraha Ramadhan; M. Andi Fikri (International Journal of Business, Law and Political Science, 2024)
General Background: Surabaya Zoo plays a critical role in wildlife conservation, education, research, and tourism, aiming to preserve biodiversity while engaging the public. Specific Background: The zoo's promotional efforts, particularly through social media platforms like TikTok, are increasingly recognized for their effectiveness in attracting visitors. The @ Surabaya Zoo Surabaya TikTok account has seen significant growth in followers and engagement, indicating a successful strategy. Knowledge Gap: Despite this success, there remains a lack of comprehensive research evaluating the relationship between TikTok promotional strategies and visitor interest, particularly through qualitative methodologies that provide deeper insights. Aims: This study aims to evaluate and improve Surabaya Zoo's promotional efforts on TikTok by employing interpretative qualitative research methods. It seeks to understand how the zoo's content affects visitor interest and engagement. Results: Preliminary findings suggest that the TikTok strategy effectively raises awareness and encourages repeat visits to the zoo. Engagement metrics, including impressions and comments, demonstrate a positive correlation with visitor interest. Novelty: This research contributes a unique perspective by linking qualitative data with promotional effectiveness on social media, particularly within the context of wildlife conservation institutions. Implications: The results provide valuable insights for Surabaya Zoo's management, offering guidance on optimizing promotional strategies through the 7Ps framework: Product, Price, Place, Promotion, People, and Process. This study underscores the importance of adaptive social media strategies in enhancing visitor engagement and promoting wildlife conservation efforts.